Methodical approaches self-assessment of quality management system in healthcare facilities - Krut, A. G.; Horachuk, V. V. (Modern medical technology, 2019)
The international standard for quality management systems and its analogue for healthcare institutions contain a requirement to analyze the quality management system. In order to fulfil, the head of the healthcare institution must carry out periodic checks of the compliance of the quality management system with the requirements of the standard and determine the level of its development. This requires an effective tool for self assessment and the development of methodological approaches to its implementation. Purpose of the study. Methodological approaches should be justified and developed for self assessment of the institution’s quality management system of a healthcare institution in accordance with the requirements of the standard «Quality management systems – EN ISO 9001:2015 for healthcare». Materials and methods. Quality management system standards international and domestic, scientific sources on the topic, the systematic approach methods, content analysis, descriptive and graphical modeling. Results. Methodological approaches to selfassessment of a quality management system are disclosed through the development of a selfassessment questionnaire, structured according to the main sections of the standard. Work with the questionnaire provides for the application of the method of comparative analysis of requirements and actual data and a rating scale from 1 to 5 points. The procedure and frequency of self-assessment is proposed. Conclusion. The proposed methodological approaches can be used in conducting a self-assessment of a quality management system to obtain reliable input for management analysis.